Perilaku Organisasi dan Efektivitas Kepemimpinan Kyai di Pondok Pesantren dalam Mengantisipasi learning loss di Masa Pandemi. - Rozzi Fatahillah (STIT AL-ISHLAH BONDOWOSO, 2021)
Concern about the occurrence of learning loss in students due to the implementation of distance learning has become a common problem that has colored the history of education in the world in general and in Indonesia in particular during this covid-19 pandemic. While all educational institutions have not found a solution to anticipate the occurrence of learning loss in students during this pandemic, the majority of Islamic boarding schools remain firm in their stance to consistently carry out face-to-face learning. So in this study, we want to see how organizational behavior at the group level, namely the teacher council (asatidz), guardians of students, and students themselves in Islamic boarding schools face organizational behavior at the individual level, namely kyai as educational leaders in Islamic boarding schools. This research is categorized in the type of library research. The approach used in this research is descriptive-qualitative. All members of the Islamic boarding school respect the Kyai's decision and are willing to cooperate with him, realizing that the Kyai's request is consistent with their personal goals. And in fact, all members of the Islamic boarding school feel that their personal goal of anticipating learning loss by continuing to hold face-to-face learning is achieved through these activities. So this is what is meant by effective leadership by a Kyai.